BI-RADS application for breast cancer screening in primary healthcare settings: assessing protocol adherence and diagnostic validity - Li, Xiang; Wang, Hong; Xu, Hui-Fang; Zhang, Shao-Kai; Zheng, Bing-Jie; Li, Hai-Liang (Frontiers in Oncology, 2025)
BackgroundThe application performance of the Breast Imaging-Reporting and Data System (BI-RADS) in primary healthcare settings remains uncertain. The normativity of BI-RADS classification and the efficacy of breast cancer detection guided by BI-RADS classification were evaluated here.MethodsAll data used in the current study were derived from a breast cancer screening cohort baseline database, which consists of 8,996 women aged 35–64 years from Central China. Participants aged 35–44 underwent automated breast ultrasound (ABUS) and handheld ultrasound (HHUS), while those aged 45–64 were screened with ABUS, HHUS, and mammography (MG). All imaging diagnoses were made by radiologists according to the BI-RADS 5th edition classification system published by the ACR in 2013. The distribution of malignant imaging findings and inter-modality agreement on BI-RADS classifications were assessed. Based on pathological results, the area under the receiver operating characteristic (ROC) curve (AUC) was used to assess the performance of breast cancer screening according to BI-RADS-guided referrals.ResultsOf individuals found with irregular morphology, 44%, 45.7% and 77.4% were classified as BI-RADS category 4 or higher for HHUS, ABUS and MG, respectively; For those with indistinct margins, the proportion was 81%, 77.5% and 40.8%, correspondingly; For grouped calcifications, they were 100% for HHUS and 85.7% for MG; Meanwhile, 72.7% and 88.9% not parallel (taller than wide) masses were categorized as BI-RADS category 4 for HHUS and ABUS. The concordance of BI-RADS classification was as high as 98.2% between HHUS and ABUS (Kappa = 0.726), whereas it was about 96% between ultrasound and MG (Kappa ranged from 0.21 to 0.25). The BI-RADS guided screening performance for breast cancer showed AUC values of 0.9935 for ABUS, 0.9529 for HHUS, 0.8983 for MG. If the BI-RADS diagnosis of MG was considered in ultrasound-negative women, only the HHUS’s performance was boosted, achieving an AUC of 0.9920.ConclusionsRadiologists at primary hospitals can effectively apply BI-RADS based on the malignant features they found. BI-RADS can provide a reliable framework for guiding breast cancer screening in primary healthcare settings.